TheimpactofvaluationrulesforintangibleassetsinJapaneseandGermanaccountsoflistedcompanies - Anne D'Arcy; Michiyo Mori; Christine Roßbach (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2003)
Intangible assets as goodwill, licenses, research and development or customer relations become in high technology and service orientated economies more and more important. But comparing the book values of listed companies and their market capitalization the financial reports seems to fail the information needs of market participants regarding the estimate of the proper firm value. Moreover, with the introduction of Anglo-American accounting systems in Europe and Asia we can observe even in the accounts of companies sited in the same jurisdiction diverging accounting practices for intangible assets caused by different accounting standards. To assess the relevance of intangible assets in Japanese and German accounts of listed companies we therefore measure certain balance sheet and profit and loss relations according to goodwill and self-developed software. We compare and analyze valuation rules for goodwill and software costs according to German GAAP, Japanese GAAP, US GAAP and IAS to determine the possible impact of diverging rules in the comparability of the accounts. Our results show that the comparability of the accounts is impaired because of different accounting practices. The recognition and valuation of goodwill and self-developed software varies significantly according to the accounting regime applied. However, for the recognition of self-developed software, the effect on the average impact on asset coefficients or profit is not that high. Moreover, an industry bias can only be found for the financial industry. In contrast, for goodwill accounting we found major differences especially between German and Japanese Blue Chips. The introduction of the new goodwill impairment only approach and the prohibition of the pooling method may have a major impact especially for Japanese companies' accounts.
urn:nbn:de:hebis:30-16967
Keywords: 330; Immaterielle Werte; Bilanzielle Bewertung; Make or Buy; Geschäftswert; Japan; Deutschland